Extracellular Vesicles of Pseudomonas: Friends and Foes - Tania Henriquez; Chiara Falciani (MDPI AG, 2023)
Extracellular vesicles (Evs) are small spherical vesicles capable of transporting molecules (such as proteins, nucleic acids and lipids) from one cell to another. They have been implicated in processes such as cell-to-cell communication, pathogenicity, biofilm formation and metabolism. In parallel, Evs have been proposed as interesting biotechnological tools. In recent years, antibiotic resistance has become a major problem for human health worldwide. A pathogen singled out as among the most lethal antibiotic-resistant organisms is Pseudomonas aeruginosa, an important Gram-negative bacterium that has been extensively studied for the production and characterization of Evs. Here, we describe the advances made in the last decade regarding understanding of the role of Evs in the pathogenicity of Pseudomonas. We also examine the potential of Evs for the development of new treatment strategies.